Critical role of diagnostic SARS-CoV-2 T cell assays for immunodeficient patients. Issue 12 (10th October 2022) - Ameratunga, Rohan; Woon, See-Tarn; Steele, Richard; Lehnert, Klaus; Leung, Euphemia; Brooks, Anna E S
Abstract : After almost 3 years of intense study, the immunological basis of COVID-19 is better understood. Patients who suffer severe disease have a chaotic, destructive immune response. Many patients with severe COVID-19 produce high titres of non-neutralising antibodies, which are unable to sterilise the infection. In contrast, there is increasing evidence that a rapid, balanced cellular immune response is required to eliminate the virus and mitigate disease severity. In the longer term, memory T cell responses, following infection or vaccination, play a critical role in protection against SARS-CoV-2. Given the pivotal role of cellular immunity in the response to COVID-19, diagnostic T cell assays for SARS-CoV-2 may be of particular value for immunodeficient patients. A diagnostic SARS-CoV-2 T cell assay would be of utility for immunocompromised patients who are unable to produce antibodies or have passively acquired antibodies from subcutaneous or intravenous immunoglobulin (SCIG/IVIG) replacement. In many antibody-deficient patients, cellular responses are preserved. SARS-CoV-2 T cell assays may identify breakthrough infections if reverse transcriptase quantitative PCR (RT-qPCR) or rapid antigen tests (RATs) are not undertaken during the window of viral shedding. In addition to utility in patients with immunodeficiency, memory T cell responses could also identify chronically symptomatic patients with long COVID-19 who were infected early in the pandemic. These individuals may have been infected before the availability of reliable RT-qPCR and RAT tests and their antibodies may have waned. T cell responses to SARS-CoV-2 have greater durability than antibodies and can also distinguish patients with infection from vaccinated individuals.